2021
DOI: 10.1097/iae.0000000000003049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glycemic Variability on the Progression of Diabetic Retinopathy Among Patients With Type 2 Diabetes

Abstract: Purpose: To evaluate the effects of glycemic variability on the progression of diabetic retinopathy (DR) among individuals with Type 2 diabetes and to test the hypothesis that consistent glycemic control delays the progression of DR.Methods: This retrospective study included 1,125 participants with a follow-up period of more than 5 years and more than 20 glucose laboratory test results. The hazard ratio of $3 steps of progression on the Early Treatment Diabetic Retinopathy Study person scale and progression to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…Similarly, there are few data on people with type 2 diabetes, and some of those also suggest no relationship [21,22]. However, recent data from a cohort of 1125 people from Park et al have produced data similar to ours, suggesting that mean HbA 1c and HbA 1c standard deviation were associated with a lower risk of retinopathy and retinopathy progression [41]. Our data suggest that there is a relationship for those with type 2 diabeteseven though we have made the assumption that the vast majority of our cohort has type 2 diabetes.…”
Section: Discussionsupporting
confidence: 68%
“…Similarly, there are few data on people with type 2 diabetes, and some of those also suggest no relationship [21,22]. However, recent data from a cohort of 1125 people from Park et al have produced data similar to ours, suggesting that mean HbA 1c and HbA 1c standard deviation were associated with a lower risk of retinopathy and retinopathy progression [41]. Our data suggest that there is a relationship for those with type 2 diabeteseven though we have made the assumption that the vast majority of our cohort has type 2 diabetes.…”
Section: Discussionsupporting
confidence: 68%
“…One meta-analysis reported that DR was associated with the long-term HbA1c variability in type 1 DM but not in type 2 DM [ 28 ]. However, recent study with a long follow-up period reported that HbA1c variability played an important role in the development of DR when the HbA1c variability was high (>0.75% [ 10 ]; the cutoff value of HbA1c SD was 1.24 [ 9 ]). One longitudinal study in Taiwan that included 3152 type 2 DM patients who were followed-up for at least 2 years showed that HbA1c variability is an independent risk factor for DR. HbA1c variability may play a role in DR development when the mean value of HbA1c variability index is >0.75% [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…One longitudinal study in Taiwan that included 3152 type 2 DM patients who were followed-up for at least 2 years showed that HbA1c variability is an independent risk factor for DR. HbA1c variability may play a role in DR development when the mean value of HbA1c variability index is >0.75% [ 10 ]. The HbA1c standard deviation was associated with a risk of ≥3 steps of progression on the Early Treatment DR Study person scale as well as progression to PDR in a Korean retrospective study that had a follow-up period of more than 5 years [ 9 ]. The optimal cutoff value of the HbA1c SD was 1.24 for PDR and ≥3 steps of progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been also suggested that diabetic patients with higher HbA1c variability are more likely to develop dementia [14]. Despite this, previous studies examining the association between HbA1c variability and the risk of DR showed inconsistent results [15][16][17][18][19][20][21][22][23][24][25][26]. In some studies, higher HbA1c variability appeared to be independently associated with DR [21,24,26], while in other studies, the association was not significant [15-20, 22, 23, 25].…”
Section: Introductionmentioning
confidence: 99%